Improvement the International Data Encryption Algorithm(IDEA)based on Chaos Theory (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background:     The (IDEA), which represents International Data Encryption Algorithm is a widely used cipher algorithm that has raised concerns due to the discovery of numerous weak keys, as highlighted in previous research. These weak keys, specifically those containing consecutive sequences of single digits, have been found to impede the algorithm's evolution and result in a sluggish avalanche effect. To address these vulnerabilities, this research aims to develop an enhanced and secure encryption algorithm by incorporating Chaos Theory principles into IDEA.Materials and methods:    The primary objective is to address the weaknesses associated with IDEA's key generation process by leveraging Chaos Theory to generate strong, highly random keys that replace the algorithm's weak keys t. The study also aims to assess the security and cryptographic strength of the enhanced IDEA algorithm through evaluations and comparisons with the original algorithm.Results:     The results showed that the proposed key passed 11 tests out of the 15 total tests, while the Traditional key of IDEA passed only 7. This indicates that the proposed method is superior by 4 tests over the Traditional method of generating keys. Also, cipher text 1 with the proposed key passed 10 tests out of the 15 total tests, while with the Traditional key passed only 8 .Conclusion:     This indicates the superiority of the proposed method of IDEA in encryption over the traditional method of IDEA.